Analisis Rasio Keuangan terhadap Harga Saham pada Perusahaan Food and Beverages - Namira Ufrida Rahmi; Andrew Andrew; Angelia Stefani; Fenita Fenita (Politeknik Ganesha Medan, 2021)
This research was conducted with the aim of examining the effect of Current Ratio, Quick Ratio, Net Profit Margin and Return on Equity on stock prices in food & beverage sector companies listed on the Indonesia Stock Exchange from 2013 to 2019. The population is the Food & Beverages sector companies listed on the IDX in 2013-2019. The sample was taken using purposive sampling method, so that the sample becomes 70 observation. This research was classified as quantitative research and the type of research is descriptive. The data analysis technique was carried out by using multiple linear regression test using the SPSS ver 25 analysis tool. The results showed that Current Ratio partially has a negative and insignificant effect on stock prices. Quick Ratio partially has a positive and insignificant effect on stock prices. Net Profit Margin partially has a positive and significant effect on stock price. And, Return on Equity partially has a negative and insignificant effect on stock prices. Meanwhile, simultaneously, Current Ratio, Quick Ratio, Net Profit Margin and Return on Equity have a positive and significant effect on stock prices in food and beverages sector companies listed on the Indonesia Stock Exchange in 2013-2019.